9a +8 -2a -3 -5a = 2a +5
Chat with our AI personalities
The expression 2a + 3 represents the sum of twice the value of a and 3. To simplify this expression, you would distribute the 2 to the a, resulting in 2a, and then add 3 to that result. Therefore, the simplified form of 2a + 3 is 2a + 3.
Oh, dude, it's like super simple. So, 2a plus 3 is just like adding 3 to twice a number, which is totally cool. So, the answer is 2a + 3. Easy peasy lemon squeezy!
(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b
(6a3 - 19a2 + 15a)/(2a - 3) = a(6a2 - 19a + 15)/(2a - 3) = a(2a - 3)(3a -5)/(2a -3) = a(3a - 5)
If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1
To simplify the expression 2a - 3 + 4b - 2a - b - 3 + 5, we first combine like terms. Combining the terms with 'a', we have 2a - 2a = 0. Combining the terms with 'b', we have 4b - b = 3b. Combining the constants, we have -3 - 3 + 5 = -1. Therefore, the simplified expression is 3b - 1.
2a + a = 3a